Metode polarisasi transmisi untuk deteksi cemaran lemak babi pada minyak goreng - Nidia Kharisma Putri; Ketut Sofjan Firdausi; Heri Sugito (Youngster Physics Journal, 2017)
This study was conducted to search for "fingerprint" of the existence of lard in vegetable  oil contaminated by lard as an evaluation of the halal of cooking oil by using transmission polarization method. The sample used was palm oil that has been mixed with chicken oil and lard. The light source used was green laser with wavelenght 532 nm. Measurement was conducted based on change of polarization transmission angle, with addition of external electric field produced by two parallel plates connected to 0-6kV DC voltage. The result shows that contaminated palm oil has greater polarization angle changes than pure palm oil. And  palm oil that has been contamined by lard has the greatest polarization angle than a pure palm oil and palm oil contaminated by chicken oil. Transmisson polarization method can be used to evaluate halal of cooking oil.Keywords: Polarization, Electrooptics,Cooking oil, Halal